The Ar-Hötöl surface rupture along the Khovd fault (Mongolian Altay) - Battogtokh Davaasambuu; Matthieu Ferry; Jean-Francois Ritz; Ulziibat Munkhuu (Journal of Maps, 2023)
ABSTRACTWe present a 1:200,000 scale map of the Ar-Hötöl surface rupture along the Khovd fault (Mongolian Altay), presumed to be the expression of the 1761 CE Mw ∼ 7.8 Great Mongol earthquake. The detailed mapping combines airborne and terrestrial imaging and topographic techniques (Sentinel-2, Pleiades, TanDEM-X, UAV and TLS) to quantify right-lateral and vertical offsets ranging from ∼ 1 m to ∼ 4 km over a length of 238 km. The smaller offsets document the deformation associated with the last surface-rupturing earthquake that affects several Bronze to Iron Age burial mounds. Their analysis yields a robust segmentation model comprising 6 segments of 20 to 51 km in length, a maximum co-seismic slip value of 4.8 m ± 0.5 m located near the center of the rupture. Our observations precise the varying kinematics along strike, bring new evidence of repeated faulting and confirm a Mw of 7.8 ± 0.3.